Screening brinjal for jassid,amrasca biguttula biguttula(ishida) tolerence - Malini C D (Department of Olericulture, College of Horticulture, 2005)
The present investigation entitled" Screening brinjal tor jassid Amrasca biguttula , biguttula (Ishida) tolerance" w 1S conducted in the Department of Olericulture, College of Horticulture, KeraJa Agricult .iral University, Vellanikkara during rabi (2004) and summer (2005). Thirty SIX brinjal accessions collected from different parts of the country were characterized for different qualitative and quantitative characters. The evaluated accessions exhibited considerable variation for growth habit, prickliness of plant parts, colour, shape and size of fruits and colour of petiole, leaves, stem and flowers. Fruit yield was maximum in FJ hybrid, Neelima and S1'.1 384. Swethe and Swetha X Haritha were early and produced maximum number of fruits per plant. Longest fruits were produced by SM 344. Fruits of SM 385 recorded maximum girth and SM 354 had hcav iest fruits. The study revealed high heritability coupled with high genetic advance for characters like fruit length, number of fruits per plant, days to last harvest and number of economic harvests. Yield was positively associated with number of fruits per plant :;JiT!ber of economic harvests and total harvests. The accessions SM 363, SM 364, SM 366, SM 384 and SM 385 were found ._<slant to jassid infestation in the field screening and under cage studies. T he morphological and anatomical bases of resistance was also studied. l ligh r • Lb hair density and longer midrib hairs were found to impart resistance in